The The Influence of Good Corporate Governance on Financial Performance with Company Size as a Moderating Variable - Noviani, Noviani Wulan Safitri; Sari, Maylia Pramono (Pusat P2M Politeknik Negeri Batam, 2026)
Financial performance is a key indicator of a company’s success in managing resources and achieving business objectives. Effective corporate governance mechanisms are essential in supporting improved financial performance. This study aims to examine the effect of the board of directors, managerial ownership, and the audit committee on corporate financial performance, with firm size as a moderating variable and capital structure as a control variable. The research population consists of manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using purposive sampling, 87 companies were selected, resulting in 261 observations. Secondary data were obtained from annual reports and financial statements accessed through the official website of the Indonesia Stock Exchange and the respective company websites. The data were analyzed using descriptive analysis and panel data regression with a fixed effect model, processed using EViews 10 software. The results indicate that the board of directors has a positive and significant effect on financial performance. In contrast, managerial ownership and the audit committee do not have a significant effect on financial performance. Furthermore, firm size is found to weaken the influence of the board of directors and the audit committee on financial performance, while it does not moderate the relationship between managerial ownership and financial performance. This study concludes that financial performance is influenced not only by internal operational factors but also by the effectiveness of corporate governance mechanisms. Firm characteristics, particularly firm size, play an important role in determining the effectiveness of corporate governance in enhancing financial performance.